A framework of IPv6 network attack dataset construction by using testbed environment - M., Zulkiflee; N., Haniza; Sahib, Shahrin; Abd. Ghani, Mohd Khanapi (2014)
IPv6 has been implemented for quite a while. Nowadays, the number of IPv6 users has gradually increased. This is due to high demand of new IP addresses allocation which IPv4 cannot offer anymore. Theoretically, IPv6 protocol is much better than IPv4 in terms of security, mobility and routing speed. Although the design of the IPv6 technology has taken security concerns into its design, the implementation of IPv6 is not a panacea for the overall security issues. New threats have been discovered due to the flaws of the IPv6 new design. In IPv4, there is a dataset called KDD’ 99 dataset which widely used to propose a new detection technique in IPv4 environment. Many intrusion detection techniques were proposed by using the KDD’99 dataset. Unfortunately till this point of time there is no available dataset which similar to KDD’ 99 in IPv6 network environment. Hence, this paper is meant to propose a framework of constructing a dataset which similar to KDD’99 dataset based on IPv6 network environment. An example of IPv6 dataset construction is explained according to the proposed framework. A testbed based on the original KDD’ 99 framework is used as a baseline platform for this study. A framework of constructing IPv6 datasets is proposed which can be encouraged researchers to produce a solid dataset for IPv6 network environment. In the future, a new dataset can be produced which can facilitate further researcher in IPv6 security domain.